2009
DOI: 10.1007/s11199-009-9631-7
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity and Cognitive Age Perception: An Examination of their Relationship and Implications for Advertising Persuasion

Abstract: This paper explores whether gender and sex role orientation, in terms of masculinity and femininity, may be associated with older cognitive age among young people. It predicts that masculinity should be associated with an older cognitive age. Two surveys (N=254 respondents aged 18-22 years and N=327 respondents aged 18-55 years), conducted in Taiwan, generally support this prediction. Moreover, this study predicts that masculinity influences people's responses to media information that contains age cues, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In the study of self-constructed gender identity, researchers classified individuals into personality categories according to their masculine and feminine scores (Beckham et al , 1988; Bem, 1974, 1977, 1981; Orlosfsky et al , 1977; Palan et al , 1999; Stevens et al , 1984). Following this approach, previous research has found that preferences and decisions made by individuals between feminine- and masculine-type identities heavily differ (Chang, 2009; Conway and Dube, 2002; Fischer and Arnold, 1994; Gould and Stern, 1993). Bem (1981) suggested that psychological gender affiliation – males who identify with more feminine personality characteristics and vice versa for females – may help explain individual differences, which we extend to include relocation decisions.…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In the study of self-constructed gender identity, researchers classified individuals into personality categories according to their masculine and feminine scores (Beckham et al , 1988; Bem, 1974, 1977, 1981; Orlosfsky et al , 1977; Palan et al , 1999; Stevens et al , 1984). Following this approach, previous research has found that preferences and decisions made by individuals between feminine- and masculine-type identities heavily differ (Chang, 2009; Conway and Dube, 2002; Fischer and Arnold, 1994; Gould and Stern, 1993). Bem (1981) suggested that psychological gender affiliation – males who identify with more feminine personality characteristics and vice versa for females – may help explain individual differences, which we extend to include relocation decisions.…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Self-concepts are multidimensional, though, and contain values and personalities, too. For example, people may have developed self-concepts oriented towards masculinity or femininity (Lenney 1991), and prior research has shown that people with masculine, feminine and androgynous self-concepts respond differently to ad messages: people with masculine self-concepts prefer relatively older models to a greater degree, and express more favourable attitudes towards ads featuring older models (Chang 2009). Such varying responses are probably triggered by value-expressive motives.…”
Section: Further Research Directionsmentioning
confidence: 99%